How does exercising make you feel? The associations between positive and negative affect, life satisfaction, self-esteem, and vitality - Faustino, Tatiana (2021)
The purpose of this study was to examine the relationship between regular physical exercise and affective responses to the behaviour, and to investigate the relationship with life satisfaction, self-esteem, and vitality. In total, 264 Portuguese exercisers (female = 157) aged between 18 and 69 years (M = 12.93; SD = 1.49) were considered for analysis in this study. Participants were regular exercisers with a mean year experience of 5.73 (SD = 3.19). Looking at the results, the structural model displayed acceptable fit to the data: χ2 (314) = 515.904; p < .001; CFI = .928; TLI = .919; RMSEA .049 [.042, .057]. Overall, significant direct effects were found as theoretically proposed, namely: exercise frequency displayed a positive and significant association with positive affect; positive affect was positively associated with life satisfaction, self-esteem, and subjective vitality; and, negative affect was negatively correlated with life satisfaction, self-esteem, and subjective vitality. Exercise frequency had a positive and significant indirect effect on life satisfaction, self-esteem, and subjective vitality via positive affect, but not via negative affect.